Performance Evaluation of Hypervisors: A Comprehensive Benchmarking Study on VMware, Xen, and KVM - Satalino, Michael; Wu, Hao; Pang, Yulei (2026 3rd International Conference on Computer and Multimedia Technology (ICCMT), 2026)
This research presents a comparative performance analysis of three prominent hypervisor architectures—KVM, Xen, and VMware Workstation—to evaluate their scalability and resource efficiency under increasing virtual machine (VM) densities. Utilizing a standardized benchmarking framework, this study quantifies performance regressing across CPU throughput (GFLOPS), memory bandwidth, disk I/O, and initialization latency. The experiment results reveal that architectural design significantly dictates scalability limits: KVM’s kernel-integrated Type-1 model achieved the highest efficiency, maintaining a near-native CPU baseline and superior I/O resilience at peak density. In contrast, Xen’s microkernel architecture demonstrated stable but lower throughput due to Domain 0 (Dom0) management overhead, while VMware’s Type-2 hosted model exhibited the most acute performance degradation. These results demonstrate that while hosted hypervisors are suitable for low-density personal use, kernel-level integration is a mechanical necessity for maintaining performance in high-concurrency server environments. This work provides a reproducible methodology and critical data for system architects and researchers seeking to optimize resource orchestration in distributed and parallel systems.
Keywords: Central Processing Unit; Cloud Computing; Hardware; Hypervisor Benchmarking; Information rates; KVM; Management information base; Measurement; Memory; Performance Evaluation; Throughput; VMware; Virtual machine monitors; Virtual machines; Virtualization; Xen; dept.csc; dept.mat

MaPP Challenge : Giving a Taste of Contemporary Mathematics Research to Secondary Students in a Puzzle‑Based Outreach Program - Lee, Younhee; Carrigan, Braxton; Clontz, Steven; Couch, P.; Jones, Cadavious; Noble, Abby; Owens, Andrew; Pang, Yulei (Mathematics Outreach: Examples and Impact from Across the Globe, 2026)
Keywords: Community‑driven; Event (particle physics); Focus (optics); Focus group; Outreach; Perception; Taste; contemporary mathematics; dept.mat; fostering positive mathematical identity; inclusive mathematical outreach program; puzzle‑ based outreach